Pembinaan Literasi Anak di Kelurahan Katimbang Kota Makassar - Masdar, Muhammad; A. Kamaruddin, Syamsu; Nonci, Nurmi; Azuz, Faidah (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
Children's literacy from elementary age to teenagers is an urgent agenda to carry out considering the rush of information through the media is increasingly being consumed by children and adolescents without selection. Therefore, it is important to develop them to be literate. This article describes service activities regarding the development of children and adolescents about the importance of literacy so that they can make a selection of the circulating information. This service activity will take place in June 2021 in Kaimbang Village, Makassar City, which is organized by Lecturers, Students, and the Literacy Observer Youth Group with participants from elementary school to junior high school age groups. The number of coaching participants is 35-35 children who are divided into 2 classes with basic materials such as Religion, Civics, Indonesian as the basic material and Social Media Insights as the core material. The presentation of the core material introduces the basic etiquette of using social media, accessing information, and disseminating it. This activity lasts 2 weeks with a meeting frequency of 3 times a week with a duration of 2-2.5 hours for each meeting. The results of the activity showed that the participants were happy and enthusiastic about learning, and they had additional knowledge about social media, especially what can and cannot be accessed according to their age and the ethics of sharing information. The conclusion of this service is that it is necessary to hold ongoing training and coaching for teenagers related to social media literacy